Percutaneous gastrostomy placement by intervention radiology: Techniques and outcome - Karthikumar, Balasubramanian; Keshava, Shyamkumar N; Moses, Vinu; Chiramel, George K; Ahmed, Munawwar; Mammen, Suraj (Indian Journal of Radiology and Imaging, 2018)
Background: Interventional radiology (IR) has played an important role in the technical evolution of gastrostomy, from the first surgical, endoscopical to percutaneous interventional procedures. Aim: This study is done to assess the technical feasibility and outcome of IR-guided percutaneous gastrostomy for patients requiring nutritional support for neuromuscular disorders or head and neck malignancies, as well as to describe simplified and newer technique for pull-type gastrostomy. Materials and Methods: This is a retrospective study including 29 patients who underwent IR-guided percutaneous gastrostomy over a period of 8 years in a tertiary-level institution. Either pull or push-type gastrostomy was performed in these patients as decided by the interventional radiologist. The procedures were assessed by analyzing the indications, technical aspects, and complications. Statistical Analysis: Descriptive summary statistics and frequencies were used to assess the techniques and related complications. Results: The sample consists of 27 patients (93%) with pull technique and 2 patients (7%) with push technique. The technical success rate was 100%. Most of the complications were minor 24% (7/29), including superficial skin infections around the tube site, self-resolving pneumoperitoneum, tube-related complications such as block, leakage, deformation, and dislodgement. Three patients (10.3%) had major complications. One patient (3.4%) developed massive pneumoperitoneum and mild peritonitis due to technical failure in the first attempt and needed re-puncture for successful placement, and other two patients (6.9%) developed peristromal focal abscess. One patient died on the third postoperative day due to type II respiratory failure. Conclusion: IR-guided percutaneous gastrostomy is a safe and effective procedure in selected patients.
Keywords: Fluoroscopy-guided percutaneous gastrostomy; percutaneous radiological gastrostomy; per-oral image-guided gastrostomy; pull-type gastrostomy; push-type gastrostomy